Pengaruh Pertumbuhan Laba, Struktur Modal dan Kinerja Keuangan terhadap Nilai Perusahaan Sektor Infrastruktur dengan Green Accounting sebagai Variabel Moderasi - Ilal Hilaliyah; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of profit growth, capital structure and financial performance on the value of infrastructure sector companies with green accounting as a moderating variable. This type of research uses quantitative research. This research uses secondary data in the form of financial reports of sample companies and determines the sample using a purposive sampling technique. Data analysis uses classical assumption tests and panel data regression. Company Value Indicators use the Tobins'q formula, Profit Growth uses Profit Growth, Capital Structure uses DER (Debt to Equity Ratio), Financial Performance uses ROA (Return on Assets), Green Accounting uses Sustainability Reports. The population of this research is Infrastructure Sector Companies listed on the BEI for the 2021-2023 period. The results of this research indicate that there is a significant positive influence between Capital Structure and Company Value in Infrastructure Sector Companies listed on the BEI.